Optimizing the Competitive Advantage of Four and Five Star Hotels in Bali with Strategic Thinking and Local Wisdom - Ni Nyoman Sudiyani; I Gusti Putu Agung Widya Goca; Cokorda Istri Agung Vera Nindia Putri; Anak Agung Istri Agung Ovy Dwijayanthi; I Kadek Eko Darma Putra (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the influence of the local wisdom of Panca Budhi Indriya on competitive advantage in 4&5-star hotels in Bali. It also investigated the mediating role of strategic thinking in enhancing the relationship between local wisdom and competitive advantage. Methodology: This study adopted a quantitative approach and used survey data collected from 158 general managers of 4&5-star hotels in Bali. Data were analyzed using Structural Equation Modeling-Partial Least Squares (Rahayu & Yanis) with SmartPLS 3 software. The study employs a structured questionnaire based on indicators developed for local wisdom, strategic thinking, and competitive advantage. Results: The findings revealed that Panca Budhi Indriya has a significant and positive influence on competitive advantage. Additionally, strategic thinking significantly mediated the relationship between Panca Budhi Indriya and competitive advantage, acting as a complementary mediator. This demonstrates that integrating local wisdom with strategic management practices enhances hotels’ competitive edge. Conclusions: This study examines the influence of local wisdom Panca Budhi Indriya on competitive advantage, both directly and indirectly through strategic thinking. The findings confirm that Panca Budhi Indriya, as a form of intangible local wisdom, significantly enhances competitive advantage. Additionally, strategic thinking acts as a complementary mediator, further strengthening this relationship. Limitations: This study was limited to 4&5-star hotels in Bali, which may not fully represent the broader hospitality sector. This quantitative approach also limits the exploration of deeper qualitative insights into the role of local wisdom in strategic management. Contribution: This study contributes to the field of tourism and hospitality management by providing empirical evidence of how local wisdom can serve as a strategic resource for achieving competitive advantage. These findings offer practical insights for hotel managers, policymakers, and academics interested in integrating cultural values into strategic planning to support sustainable tourism development.